The facilitators of interagency working in the context of European public service reform. Issue 5 (23rd November 2020) - Connolly, John; Barnes, Jacqueline; Guerra, Joana; Pyper, Robert
ABSTRACT: This article provides an overview of key lessons about the governance and leadership of interagency working in multi-level contexts. The article is based on interviews with local and national leaders across Europe. This topic is timely given the complexity of European public sector governance which demands leadership, co-production, and styles of collaboration which promote partnership-working within local contexts. We highlight that localism is central but this still requires national political leadership for localism to be managed and delivered effectively. In other words, empowerment-heavy models of governance, without top-down support, risks interagency ineffectiveness or even failure. We argue that leadership at macro, meso and micro levels of the governance system is required in order for successful interagency working to be delivered. We find that removing the barriers to interagency working requires the identification of an interagency leader (and to even enshrine this within statute), clear roles and lines of accountability for professionals, a breakdown of disciplinary silos, non-tokenistic bottom-up approaches, national public service leadership which promotes capacity building, and the dovetailing of planning and evaluation. The article concludes by proposing strategies for developing effective multi-level interagency working.